Bioefficacy of Selected Biorational Insecticides against Whitefly, Bemisia tabaci Gennadius in Brinjal - Uddin, Mohammad Mahir; Hena, Most Hasna; Rahman , Md Mahbubur; Das, Gopal (Journal of the Bangladesh Agricultural University, 2025)
Whitefly (Bemisia tabaci Genn.) is a serious sucking pest which causes significant damage of brinjal in Bangladesh. An experiment was conducted at the Entomology Field Laboratory, Bangladesh Agricultural University, Mymensingh during October to March to evaluate the efficacy of selected biorational insecticides viz. Award 40 SC (Buprofezin); Neem oil extract (Azadiractin); Bioneem plus 1% (Azadiractin); Suspend 5 SG (Emamectin benzoate); Tracer 45 SC (Spinosad) and Imidagold 20 SL (Imidacloprid) against whitefly in brinjal. the research was done in RCBD design with three replications of each treatment. Three sprays were applied on the pest infested plants and data were collected on 3, 5 and 7 days after each spray. Data were collected on no. of nymph & adult leaf-1, total no. of infested leaf & twig plant-1. Among the tested biorational insecticides, Buprofezin showed the best efficacy in reducing pest population after all sprays. In case of percent reduction of nymph on leaf over control, a remarkable decrease of 77.81%, 67.53% and 79.13% was observed from 1st, 2nd and 3rd sprays, respectively. In case of percent reduction of adult whitefly on leaf over control, 71.33%, 67.76% and 57.72% was recorded after 1st, 2nd and 3rd sprays, respectively. The highest reduction of leaf and twig infestation was also noticed in Buprofezin treated plots. Mean percent reduction of infested leaf over control was 48.81%, 53.19% and 49.46% from 1st, 2nd and 3rd sprays, respectively. The mean percent reduction of twig infestation over control was 41.21%, 36.42% and 31.76% after 1st, 2nd and 3rd sprays, respectively in Buprofezin treated plants and 48.21%, 34.38% and 17.62% after 1st, 2nd and 3rd sprays, respectively in Bio-neem plus treated plants. Therefore, Buprofezin could be used as the best management practice for whitefly in brinjal ecosystem. J Bangladesh Agril Univ 23(4): 491–497, 2025